Shi'i Communities in Southeast Asia: Religious Harmony Institutions and Peaceful Sunni-Shia - Alkaff, Syed Huzaifah Bin Othman; Jani, Muhammad Haziq Bin (Faculty of Islam Nusantara, Nahdlatul Ulama University of Indonesia (Unusia) Jakarta., 2023)
This study examines the dynamics of Sunni–Shiʿi relations in Singapore, focusing on the Ismaili and Imami Shiʿi communities within a political culture that emphasizes religious harmony and pluralism. It challenges the assumption that Sunni–Shiʿi differences are inherently irreconcilable by situating sectarian relations within Singapore’s specific socio-political context. The research employs a qualitative descriptive-comparative approach. Primary data were collected through semi-structured interviews with religious leaders, academics, administrators of inter-madhhab dialogue institutions, and representatives of both Sunni and Shiʿi communities. Secondary data were gathered through a comprehensive review of scholarly publications, books, policy documents, and civil society reports addressing Sunni–Shiʿi relations. Data were analyzed thematically to identify patterns and variations in intra-faith harmony practices, with source triangulation applied to ensure validity. The findings indicate that Sunni–Shiʿi relations in Singapore have historically been peaceful within the country’s secular-pluralistic political framework. The Ismaili community, as the oldest Shiʿi group, adapted during Singapore’s nation-building phase, while the Imami community, which expanded after the Iranian Revolution, has operated within an already established legal and cultural framework of religious harmony. Episodes of tension are largely attributable to the intrusion of external political sentiments, particularly those linked to Middle Eastern conflicts, rather than domestic factors. These findings suggest that intra-faith harmony is strongly shaped by national institutional and political contexts. In a system that safeguards religious freedom and promotes interreligious harmony, sectarian differences can be constructively managed within a plural society.